Genomic properties of Marine Group A bacteria indicate a role in the marine sulfur cycle - Wright, Jody J (Nature Publishing Group, 2014)
Marine Group A (MGA) is a deeply branching and uncultivated phylum of bacteria. Although their functional roles remain elusive, MGA subgroups are particularly abundant and diverse in oxygen minimum zones and permanent or seasonally stratified anoxic basins, suggesting metabolic adaptation to oxygen-deficiency. Here, we expand a previous survey of MGA diversity in O(2)-deficient waters of the Northeast subarctic Pacific Ocean (NESAP) to include Saanich Inlet (SI), an anoxic fjord with seasonal O(2) gradients and periodic sulfide accumulation. Phylogenetic analysis of small subunit ribosomal RNA (16S rRNA) gene clone libraries recovered five previously described MGA subgroups and defined three novel subgroups (SHBH1141, SHBH391, and SHAN400) in SI. To discern the functional properties of MGA residing along gradients of O(2) in the NESAP and SI, we identified and sequenced to completion 14 fosmids harboring MGA-associated 16S RNA genes from a collection of 46 fosmid libraries sourced from NESAP and SI waters. Comparative analysis of these fosmids, in addition to four publicly available MGA-associated large-insert DNA fragments from Hawaii Ocean Time-series and Monterey Bay, revealed widespread genomic differentiation proximal to the ribosomal RNA operon that did not consistently reflect subgroup partitioning patterns observed in 16S rRNA gene clone libraries. Predicted protein-coding genes associated with adaptation to O(2)-deficiency and sulfur-based energy metabolism were detected on multiple fosmids, including polysulfide reductase (psrABC), implicated in dissimilatory polysulfide reduction to hydrogen sulfide and dissimilatory sulfur oxidation. These results posit a potential role for specific MGA subgroups in the marine sulfur cycle.